Modified Titanium Content in Titanosilicates Mesoporous Molecular Sieves MCM-41 as Selective Catalyst for Epoxidation of Alkenes (Journal of Sciences, Islamic Republic of Iran)
Ti-MCM-41 was synthesized at pH 3, 7 and 11. The titanium content was determined by AAS and found to be 4%, 3.2% and 4.5%, respectively. In order to increase the titanium content in Ti-MCM-41, Ti(IV) ions were grafted onto Ti-MCM-41 using TiCl4 in toluene and Ti(OBu)4 in ethanol. The incorporation of Ti was determined to be 28% and 30%, respectively. The oxidation of olefins such as cyclopentene, cyclohexene, norbornene and trans-2-hexene-1-ol with TBHP in the presence of Ti-grafted Ti-MCM-41 were carried out in CHCl3. This system successfully catalized the oxidation of these olefins toward the corresponding epoxides with 60 to 90% reactivity and 95 to 100% selectivity